Determination of mercury in urine by atomic absorption spectrometry - Kešeljević, Bojan; Huremović, Jasna; Sulejmanović, Jasmina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2012)
Urine is a liquid waste product of the body. Substances that are ingested and fail to be apsorbed are excreted, solid waste through the intestines, the urine through the kidney and ureter and another fluid from the body through perspiration. Determination of mercury content of urine is not included in routine examinations, but mercury can be present in urine at concentrations that could have serious effects on human health. Urine donors were selected in regard to their occupations, age, lifestyle habits, and different diet, with special reference to dental professionals, consumers of marine food and smokers, as a group of subjects that could have a higher concentration of this metal. To determine the mercury content in urine ,atomic absorption spectrometry – a technique of cold vapor method was used The total content of mercury in 76 analyzed urine samples was in the range of 0.12 to 12.24 ng/mL. There was a positive correlation between the number of teeth with amalgam fillings and urinary concentrations of mercury in some donors,. In contrast, the other analyzed factors that theoretically can affect the levels of mercury in urine, did not show such correlation.